Investment Subsidies and Time-Consistent Environmental Policy. - Lisandro Abrego; Carlo Perroni (University of Copenhagen, Economic Policy Research Unit (EPRU), 1999)
We describe a model of dynamic pollution abatement choices with heterogeneous agents, where, due to the presence of a distributional objective and to the absence of incentive-compatible compensation mechanisms, the choice of a second-best level of emission taxation is time-inconsistent. In this model, we investigate whether investment subsidies can act as a substitute for policy commitment.
Keywords: 330